Forensic Autopsy is reviewed from the Aspects of Ethics, Medicolegal and Humanities - Taufik Suryadi; Kulsum Kulsum (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This article is motivated by the importance of learning about forensic autopsy. A forensic autopsy is carried out on the body of someone suspected of dying due to an unnatural cause such as in cases of accidents, homicides, or suicide. Forensic autopsy includes external and internal examinations relating to respect for a deceased human body. The controversy surrounding autopsy often occurs in the community. For reasons of culture, customs and religion, there is often a refusal to do autopsy. This article discusses the importance of autopsy and aspects related to ethics, humanities and medicolegal. The medicolegal police asked to do a forensic autopsy on forensic medicine experts to find the cause of death of the victim. The purpose of this article explains about the ethical, medicolegal and humanities aspects related to forensic autopsy.